Brown Bear (Ursus arctos) Predation of Broad Whitefish (Coregonus nasus) in the Mackenzie Delta Region, Northwest Territories ... - Barker, O.E.; Derocher, A.E. (University of Alberta Library, 2009)
On 2 October 2007, we observed evidence of at least one brown bear (Ursus arctos) predating and caching broad whitefish (Coregonus nasus) at Pete’s Creek, a tributary of the Mackenzie River, Northwest Territories. While predation on whitefish by brown bears has been reported as traditional ecological knowledge in the Northwest Territories, accounts in the scientific literature of brown bears feeding on fish other than salmon, trout (Oncorhynchus spp.), and charr (Salvelinus spp.) are rare, particularly for North America. As a spatially concentrated, high-quality food in a resource-poor landscape, migrating broad whitefish may play an important role in the foraging ecology of some Arctic brown bears. ...